PENETAPAN KANDUNGAN FENOLAT TOTAL DAN UJI AKTIVITAS ANTIOKSIDAN MENGGUNAKAN RADIKAL DPPH FRAKSI ETIL ASETAT SARI BUAH APEL BELUDRU (Diospyros blancoi A. DC.) - Johannes Baptista Yunio Rahmawan; Yohanes Dwiatmaka (Sanata Dharma University, 2013)
Abstract: Antioxidant plays a role in inhibiting oxidation by binding to free radicals. As a result,the cell damage that leads to degenerative diseases can be inhibited. This research wasconducted to determine the antioxidant activity and total phenolic content of ethyl acetatefraction of velvet aple (Diospyros blancoi A.DC.) juice. Previously known that other plants fromgenus Diospyros contain phenolic compounds such as quercetin. Antioxidant activity testperformed qualitatively and quantitatively using radical of 1,1-diphenyl-2 pikrilhidrazil(DPPH) and expressed as the value Inhibition Concentration 50 (IC50). Determination of totalphenolic using Folin-Ciocalteu method expressed as equivalent mass of gallic acid. Phenoliccompounds will be oxidized by the Folin-Ciocalteu under alkaline conditions, forming a bluesolution. The results showed that the ethyl acetate fraction of velvet apple juice has very strongantioxidant activity with IC50 of (30.0 0.09) mg / mL. Total phenolic content of (393.5 0.35) mggallic acid equivalents per gram of ethyl acetate fraction.Keywords: antioxidant, velvet apple (Diospyros blancoi A. DC), ethyl acetate fraction, DPPH,total phenolic content.